Pompei. - Pain, James & sons. [from old catalog]; Rive, Robert; Yudin Collection (Library of Congress) ([S.l. : s.n., 1880)
Photographs (with Italian captions) show ruins in the extinct city of Pompei, Italy.
Decorative photograph on title page signed: Robert Rive, Naples.
Keywords: Archaeological sites -- Italy -- Pompeii (Extinct city) -- 1880-1890.; Pompeii (Extinct city) -- Photographs -- 19th century; Photograph albums -- 1800-1890.